What literacy for Africa? - (:unkn) unknown (My University, 2024)
This article presents literacy in sub-Saharan Africa. It sets out the particular context, which is very different from the context of literacy in Europe. It discusses the definition of a literate person, then the variety of literacy practices, which correspond to different philosophies. A quantitative estimate of the needs and a typology of the target groups is made, before looking at the diversity of the players and structures involved in the various countries, using Mali as an example. Finally, the question of languages is addressed.
Keywords: African Research